Direct Asymmetric Aldol Reaction Catalyzed by C2-Symmetrical Chiral Primary Amine Organocatalysts - Zhu, Gong-Jian; Da, Chao-Shan; Jia, Ya-Ning; Ma, Xiao; Yi, Lei (Letters in Organic Chemistry, 2010)
Three novel C2-symmetrical chiral primary amines were synthesized from chiral BINOL and diamines. Then their catalytic activities in the asymmetric aldol reactions were evaluated, and the result indicated that 1c was the optimal organocatalyst. The reaction of a variety of aromatic aldehydes with aliphatic ketones, catalyzed by 20 mol % 1c in the addition of benzoic acid in carbon tetrachloride, afforded the aldol products in high yields (up to 92%) and good enantioselectivities (up to 71%).
Keywords: C2-symmetry